The Signals of the financial crisis - HAMIDOUCHE, M’hamed; BEKKOUCHE, Karima (Advances in Social Sciences Research Journal, 2019)
The relationship is complex between the economic crisis, which signifies a slowing-down of economic activity (recession or depression) and affects all economic actors (households, consumers, firms, administrations, savers, banks and investors), on one side. And the financial crisis, which refers to the destabilization of the banking and financial system of one or more economies and which affects the currencies, the stock market, the households and the banks or the States in the event of over-indebtedness on the other side. This relationship depends on the scale of the crisis in the affected market and the fettering of risks involved in combination with other markets. However, the history of the crises converges on the ascertainment that over liquidity weakens the economic and financial system by accelerating credit, thus creating a gap between prices and their fundamental values. Nevertheless, no academic consensus was reached on the premises of the crisis, notwithstanding, the values of indicators such as the GDP, the economic growth, the Dow Jones index, the VIX and the interest rates or others that precede the crisis conferring a signification to the advent of the crisis. Thus, fiscal and monetary policies aimed to control aggregate demand and which interlock with the conditions and the causes of crises, for this reason can be identified by signals described as weak, medium or strong.